Development of blind frame synchronization for transfer system with differential space-time block coding - Tokar, Mikhail (Technology audit and production reserves, 2019)
The object of this research is the methods and algorithms for frame synchronization used in multi-antenna radio systems (Multiple Input Multiple Output – MIMO). The implementation of radio communication systems and, in particular, MIMO, implies that the demodulator synchronizes the phase of the reference carrier and the time of signal processing processes. Time synchronization is divided into symbolic and frame synchronization. As for the synchronization of the reference carrier and symbol synchronization, these types of synchronization are provided by traditional methods and are not considered in this paper. The frame synchronization in the vast majority of cases is provided by the use of pilot signals (sync words). At their core, they are markers and are periodically embedded in the data stream to indicate the beginning of another new data block. The resources of the transmission system, spent on the transmission of pilot signals, are not used to transmit user information, as a result of which the efficiency of using the time-frequency resource of the system is degraded. To a lesser extent, there are so-called «blind» signal processing methods based on the redundancy properties of the transmitted signal. These methods have no drawbacks from the use of pilot signals and are divided into methods for assessing the state of the communication channel, signal identification, and synchronization. Based on this, such methods are of practical interest. In this work, let’s propose a frame synchronization method for demodulating differential space-time block coding signals using MIMO technology. The synchronization algorithm does not require the use of preambles and sync words, which ensure efficient use of the time-frequency resource. An analysis of the structure of the algorithm and the simulation results show its performance at low signal-to-noise ratios in the transmission system. The algorithm does not require knowledge of the state of the communication channel, has low computational complexity compared to existing analogues, and allows implementation with a different number of transmitting and receiving antennas.